A square planar copper(II) complex noncovalently conjugated with a p-cresol for bioinspired catecholase activity - Mukherjee, Subham; Sarkar, Gayetri; De, Abhranil; Biswas, Bhaskar (European Journal of Chemistry, 2023)
This work presents the synthesis of an unprecedented p-cresol-conjugated copper(II) complex as a p-cresol-coupled polydentate ligand, its crystal structure, and catecholase activity. X-ray crystallography reveals that the Cu(II) centre adopts a nearly planar coordination geometry. Crystal data for C14H13Cu0.5O3: Monoclinic, space group P21/c (no. 14), a = 5.9204(2) Å, b = 21.5615(10) Å, c = 9.0715(4) Å, β = 91.266(4)°, V = 1157.72(8) Å3, Z = 4, μ(MoKα) = 0.987 mm-1, Dcalc = 1.498 g/cm3, 12647 reflections measured (6.884° ≤ 2Θ ≤ 63.42°), 3233 unique (Rint = 0.0618, Rsigma = 0.0512) which were used in all calculations. The final R1 was 0.0710 (I > 2σ(I)) and wR2 was 0.2173 (all data). The crystallized p-cresol was localized in complex units through intermolecular O···H interactions and formed a 3D supramolecular framework employing short-ranged O···H and C-H···π interactions in the solid state. The copper(II) complex has been evaluated as a bioinspired catalyst in the oxidative transformation of 3,5-di-tert-butylcatechol (DTBC) to o-benzoquinone in acetonitrile with a high turnover number, 2.26´104 h–1. Electrochemical analysis of the copper(II) complex in the presence of DTBC recommends the generation of a catechol/o-benzosemiquinone redox couple during catalytic oxidation with the generation of hydrogen peroxide as a byproduct.